1990
DOI: 10.1104/pp.94.2.470
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Elevated Ultraviolet-B Radiation and CO2 on Productivity and Photosynthetic Characteristics in Wheat, Rice, and Soybean

Abstract: Wheat (Triticum aestivum L. cv Bannock), rice (Oryza sativa L.cv , and soybean (Glycine max [L.] Merr cv Essex) were grown in a factorial greenhouse experiment to determine if C02-induced increases in photosynthesis, biomass, and yield are modified by increases in ultraviolet (UV)-B radiation corresponding to stratospheric ozone depletion. The experimental conditions simulated were: (a) an increase in CO2 concentration from 350 to 650 microliters per liter; (b) an increase in UV-B radiation corresponding to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(78 citation statements)
references
References 16 publications
4
71
1
2
Order By: Relevance
“…2C), it is concluded that higher UV-B radiation (16 kJ m −2 per day) has both direct and indirect effects on cotton leaf photosynthesis. Similar reductions in photosynthesis were observed in other crop species such as soybean (Vu et al, 1981) and rice (Teramura et al, 1990). Nogues et al (1999) also reached a similar conclusion that there is a direct effect of UV-B radiation on stomatal conductance in addition to that caused by changes in mesophyll photosynthesis of pea, Asiatic dayflower (Commelina communis L.), and oilseed rape (Brassica napus L.) plants.…”
Section: Temporal Photosynthesis Trendssupporting
confidence: 60%
See 1 more Smart Citation
“…2C), it is concluded that higher UV-B radiation (16 kJ m −2 per day) has both direct and indirect effects on cotton leaf photosynthesis. Similar reductions in photosynthesis were observed in other crop species such as soybean (Vu et al, 1981) and rice (Teramura et al, 1990). Nogues et al (1999) also reached a similar conclusion that there is a direct effect of UV-B radiation on stomatal conductance in addition to that caused by changes in mesophyll photosynthesis of pea, Asiatic dayflower (Commelina communis L.), and oilseed rape (Brassica napus L.) plants.…”
Section: Temporal Photosynthesis Trendssupporting
confidence: 60%
“…In addition to the intensive investigations on growth and physiological responses to UV-B radiation on many field crops such as bean (Phaseolus vulgaris L.) (Deckmyn et al, 1994), maize (Zea mays L.) (Correia et al, 1998(Correia et al, , 1999Mark and Tevini, 1996), pea (Pisum sativum L.) (Day et al, 1996;Mepsted et al, 1996), rice (Oryza sativa L.) (Dai et al, 1992;Teramura et al, 1990), soybean [Glycine max (L.) Merr.] (Miller et al, 1994;Sinclair et al, 1990;Teramura et al, 1990), sunflower (Helianthus annuus L.) (Battaglia and Brennen, 2000), and wheat (Triticum aestivum L.) (Li et al, 2000;Teramura et al, 1990), several reviews have recently summarized the effects and consequences of UV-B radiation on major agricultural and horticultural crops, and nonagricultural species (Allen, 1990(Allen, , 1994Allen et al, 1998;Caldwell et al, 1998;Groth and Krupa, 2000;Krupa and Kickert, 1989;Teramura and Sullivan, 1994). The inferences from these studies and reviews are that plant sensitivities to UV-B radiation differ among species and cultivars within a species; however, little is known about the responses of cotton (Gossypium hirsutum L.), a major economic crop grown on over 32 Mha worldwide and over 5 Mha in the United States (http://www.ers.usda.gov/briefing/cotton).…”
Section: Introductionmentioning
confidence: 99%
“…One-third to one-half of all plant species tested are deleteriously affected by UV-B levels "above ambient" (Sullivan, 1992). A substantial number of studies have been conducted that have evaluated the potential consequences of an increase in UV-B radiation on many plants (Tevini et al, 1981;Teramura et al, 1990;Miller et al, 1994;Caldwell et al, 1998;Correia et al, 1998Correia et al, , 1999Li et al, 2000, Searles et al, 2001), but we have a rather limited understanding of the role that UV-B radiation plays in controlling cotton growth, development, yield and quality. Searles et al (2001) searched for "all suitable published studies" with field-based measurements of UV-B influences on vascular plants and found no studies on cotton.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, global climate changes that might negatively affect agricultural M.A. El-Sharkawy productivity in many parts of the world would further aggravate deficits in future food supply (Quebedeaux, 1990;Teramura, 1990;Teramura et al, 1990;Titus, 1990;Wittwer, 1990;Rosenzweig and Parry, 1994). Rosenzweig and Parry (1994), in assessing the effects of climate changes on cereal production, found that it will increase the current disparities between developed and developing countries.…”
Section: Funding Basic Research In Agriculture Is Warrantedmentioning
confidence: 99%
“…But it is necessary here to point out a few of the many positive achievements and contributions of basic research in the fields of plant and crop physiology that have been translated so far into gains in agricultural productivity through plant breeding and management of cropping ecosystems. Furthermore, in view of the increasingly changing global climate, the role of plant and crop physiological research in characterizing and predicting responses of a given plant and crop species as well as natural and agricultural ecosystems performances under these dynamically changing environmental conditions will be even greater (Hesketh et al, 1984;Begonia et al,1987Begonia et al, ,1996Begonia et al, ,1999Bazzaz, 1990;Besford et al, 1990;Teramura et al, 1990;Idso et al, 1991;Ziska et al, 1991;Acock and Acock, 1993;Chen et al, 1993, Gifford andMorison, 1993;Hall and Allen, 1993;Patterson, 1993;Sinha, 1993;Rosenzweig, 1993;Rosenzweig and Parry;Bunce and Sicher, 2004;Sholtis et al, 2004;Long et al, 2006).…”
Section: Why Should Mavericks and Dissenters Be Tolerated? A Few Exammentioning
confidence: 99%